Progress in Nanotechnology 2009
DOI: 10.1002/9780470588260.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanosilica Additions on Belite Cement Pastes Held in Sulfate Solutions

Abstract: Fly Ash Belite cement (FABC) pastes with and without nanosilica additions have been prepared and maintained in sulfate solutions (Na 2 SO 4 0.5 M) for 180 days. The mechanical performance and the changes in microstructure have been monitored at 28, 90 and 180 days by compressive strength, X-ray diffraction (XRD) and 29 Si MAS NMR measurements. We have found that, unexpectedly, and contrary to what happens in Ordinary Portland Cements (OPC), the addition of nanosilica particles induces an initial fall in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…When incorporating NS in ordinary cement paste, the NS content, water-to-binder ratio (W/B), and curing time were found to be critical to increase the compressive strength by many researchers [14][15][16]. Dolado et al [17] reported that the compressive strength increase progressively with the increase of NS content within the range from 0.2% to 12% by mass of cement. With respect to pastes not containing NS, it was found that strength gains up to 65% higher could be achieved.…”
Section: Introductionmentioning
confidence: 97%
“…When incorporating NS in ordinary cement paste, the NS content, water-to-binder ratio (W/B), and curing time were found to be critical to increase the compressive strength by many researchers [14][15][16]. Dolado et al [17] reported that the compressive strength increase progressively with the increase of NS content within the range from 0.2% to 12% by mass of cement. With respect to pastes not containing NS, it was found that strength gains up to 65% higher could be achieved.…”
Section: Introductionmentioning
confidence: 97%
“…The calcium silicate hydrate (C-S-H) is the most important hydration product contributing the mechanical properties of Portland cement. It has been demonstrated that the short term and long term compressive strength of Portland cement system can be greatly enhanced by formation of calcium silicate between silica and calcium hydroxide [17,29]. Silica behaves as an activator to promote pozzolanic reaction with calcium hydroxide to form calcium silicate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in-situ pozzolanic formation of calcium silicate hydrate from silica particles and calcium hydroxide has been used to reinforce the mechanical properties of Portland cement [17,18]. The pozzolanic reaction occurred during the hydration process at room temperature to produce calcium silicate hydrate, one of the major components of Portland cement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the difference in enhancing compressive strength diminishes over time. Another interesting observation is that the strength of NS@PCE-1-added sample is lower than the reference at the age of 12 h. It is reported that NS addition would lead to high-polymerized C-S-H gels [22,23]. For a series of NS@PCE, at specific time, they may produce C-S-H gels with different quantity or quality, which may be another mechanism accounting for compressive strength enhancement.…”
Section: Effect Of Nanostructure Of Ns@pcementioning
confidence: 93%